ANALISIS KETAHANAN PADI GOGO DAN PADI SAWAH (Oryza sativa L) TERHADAPEMPAT RAS PENYAKIT BLAS (Pyricularia grisea Sacc) - Sri Indrayani; Anggriani Nasution; Enung Mulyaningsih (AGRICOLA, 2013)
Blast disease caused by the fungus Pyriculariagrisea is a disease that can infect of upland rice and lowland. Consequently  this disease, significantly reduce the productivity of rice plants. The use of resistant varieties is the most efficient way to control this disease. Resistant varieties will be able to maintain yields and reduce pesticide use. To create resistant varieties, information about resistance line/ variety as a candidate of parental is needed.   Therefore it is necessary to test resistance level of lines/ varieties. The aim of research was to determine the resistance level of local lines of rice / lines superior potential / national varieties of four dominant races blasIndomesia Total number of sampleswas 22 lines / varieties and four blastraces (033, 073, 133, and 173). The result showedthat eight upland rice lines were resistant to race 033 and one strain (ketanhitam) wasresistant to two races (033 and 173). While the lowlandrice,only one line (BojongJengkolSurade), showed a response resistant to race 033. Upland rice showed higher resistance (44%) than lowland rice (25%) to one race blas 033. These Lineshave the potential as a parent  to produce a blastresistancerice progenies.